Plant Parasitic Nematode Abundance and Diversity in Potato (Solanum tuberosum) Cultivation at Various Altitudes in Wonosobo and Banjarnegara - Khairunnisa Lubis; Siwi Indarti; Nugroho Susetya Putra (Universitas Gadjah Mada, 2021)
Plant-parasitic nematodes are one of the causes of yield loss in potato cultivation. Currently, information on the diversity, abundance, and dominance of potato parasitic nematode genera is not available. This research aimed to determine the pattern of distribution, abundance, and dominance of parasitic nematode genera on potato plant (Solanum tuberosum) in Wonosobo and Banjarnegara Districts at various altitudes i.e.: 1,250–1,500; 1,500–1,750; 1,750–2,000; and 2,000–2,250 meters above sea level (m.a.s.l.). Soil rhizosphere and root samples were collected, and nematodes were extracted using the Whitehead tray modification technique. The nematodes were adjusted with Formalin Acetic acid Alchohol (FAA), mounted, and identified based on morphological characters. The diversity index was determined to distinguish plant-parasitic nematode diversity. Six genera of potato plant-parasitic nematodes were found, namely Meloidogyne, Hirschmanniella, Globodera, Criconemoides, Helicotylenchus, and Xiphinema. The highest population of plant-parasitic nematodes was found at 1,250–1,500 m.a.s.l. from both root and soil samples. The nematode populations were 56.67 nematodes/5 g root and 103.33 nematodes/100 g of soil. The abundance of parasitic nematodes did not differ significantly among different altitudes in both districts. The dominant parasitic nematodes in soil samples were Meloidogyne with 16.78%, while Globodera was 13.98%. The Shannon-Wiener index implied that the diversity of parasitic nematodes of potato plants and stability of community in Wonosobo and Banjarnegara Districts were categorized as low.